Program management in defense and high tech environments - McCarthy, Charles Christopher (Best practices and advances in program management series, 2016)
This book illuminates the entire life cycle of program management from the customer's original concept to successful completion. It includes many helpful ideas and insights into why programs and program managers can fail and provides insights about how program managers can succeed. It is orgnized as a chronological "tale" of a program life cycle, with "side trips" that cover important concepts of leadership, claims and claims avoidance, earned value measurement (EVM), communication basics, negotiations, and coaching. Topics include: overview of program management; role of program managers, their required skills and experience and types of programs and contracts; program manager's role and environment. McCarthy uses true-to-life stories to present the nuts and bolts of the work to illustrate the science of program management and the art that is necessary for success